Etika Max Scheler: Kritik Atas Formalisme Kant - Agus Darmaji (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
This article addresses Max Scheler’s critique of Kant’s formalistic ethics. Through phenomenology, he attempts to reconstruct and develop the problem of values in general, especially ethics. He believes that in this way, ethics can avoid psychological, sociological, and historical relativism. Scheler aims to offer a critical assessment of Kant’s formal ethics and seeks to overcome Kant’s formalism by proposing thoughts on material ethics.